Real-Time Biosensor Platform Based on Novel Sandwich Graphdiyne for Ultrasensitive Detection of Tumor Marker - Xu, Jing; Liu, Yinbing; Huang, Ke-Jing; Hou, Yang-Yang; Sun, Xiaoxuan; Li, Jiaqiang (Analytical chemistry (Washington), 2022)
Realization of a highly sensitive analysis and sensing platform is important for early-stage tumor diagnosis. In this work, a self-powered biosensor with a novel sandwich graphdiyne (SGDY) combined with an aptamer-specific recognition function was developed to sensitively and accurately detect tumor markers. Results indicated that the detection limits of microRNA (miRNA)-21 and miRNA-141 were 0.15 and 0.30 fM (S/N = 3) in the linear range of 0.05-10000 and 1-10000 fM, respectively. The newly designed platform has great promise for early-stage tumor diagnosis.